Legal Protection and Children's Rights based on the 1945 Constitution in the Dynamics of Government in Indonesia - Rivaldi, Ahmad (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2024)
This research examines the legal protection of children's rights in Indonesia with a focus on the implementation of the 1945 Constitution. The main problems include weak law enforcement institutions, lack of resources, and political intervention. The aim of the research is to identify challenges in protecting children's rights and evaluate the effectiveness of the legal framework as well as provide recommendations for strengthening the protection of children's rights through legal reform, increasing institutional capacity, and protecting witnesses and victims. The method used is normative legal research with a statutory and conceptual approach, involving analysis of legal norms, literature studies, and interviews with child rights experts. The research results show a discrepancy between written law and practice in the field, influenced by weak law enforcement institutions, lack of resources, and political intervention. This research emphasizes the need to strengthen institutions, increase resources, education and training, as well as protect witnesses and victims with the support of strong political commitment to ensure the effectiveness of the law.